Comparison of curative effect between different retrograde filling materials in young permanent molar root canal therapy - Qi, Fengna; Sun, Honglei; Zhang, Li; Zheng, Jingwei (Cellular and Molecular Biology, 2022)
The first mandible and maxilla permanent molars are the first permanent teeth that grow next to the deciduous teeth and may decay due to carelessness. Their caries can spread to the pulpal tentacles and cause pulpal and periapical diseases. In the current study, we tried to compare the curative effect of different retrograde filling materials, i.e. white MTA, gray MTA, Portland cement, and IRM, in young permanent molar root canal therapy. Because IL-1β stimulates bone degradation by osteoclasts, IL-1β gene expression was also measured for further evaluation. For this purpose, 400 students (240 boys and 160 girls) aged 8 to 11 years referred to the Pediatric Dental Center for first permanent molar root canal therapy were selected during two years. After recording the demographic characteristics of each patient, the first permanent molar teeth were examined by a general dentist with Abslang and decayed teeth were considered to have both discolorations in their grooves and apparent opacity. The patients, who need root canal therapy, were divided into four groups. The first group was treated with gray MTA. The second group was treated with white MTA. The third group received Portland cement for root canal therapy. The fourth group was treated with IRM. Also, IL-1β gene expression was evaluated by the real-time PCR technique. Relative changes in gene expression in PBMC cells were performed using One Way ANOVA. SPSS 18 software was used to determine the correlation of gene expression in PBMCs. The results showed that there was no significant difference between the groups in terms of age (p = 0.12) and gender (p = 0.24). Also, the need for endodontic treatment in the mandible (n = 278) was higher than the maxilla (n = 85) and both jaws (n = 37). But there was no significant difference between the groups in terms of the need for endodontic treatment (p = 0.32). The results of Pearson correlation coefficients between studied groups in terms of IL-1β gene expression showed that gray MTA and white MTA were not statistically different, but MTAs were generally different from Portland cement and IRM, with higher IL-1β gene expression. In general, the results showed that the teeth in the vicinity of gray MTA and white MTA showed a more appropriate response than Portland cement and IRM, so the use of MTA and its preference over other materials is recommended. In the case of Portland cement, more studies are needed to reach a conclusion comparing this material with MTA.